Optimal Time for Withdrawal of Voluntary Retirement Scheme with a Probability of Acceptance of Retirement Request (Journal of Information Technology and Digital World, 2020)
Voluntary retirement schemes are observed in certain sectors of the Indian Industry such as Banking and Insurance. There is a need to determine the optimal time to withdraw a voluntary retirement scheme (VRS), balancing the reduction of high compensation of a segment of employees, prevent mass voluntary turnover from the grade, achieve optimal productivity and ensure normal business operations. In this paper an approach to derive an optimal policy to withdraw a voluntary retirement scheme considering a probability of acceptance of a retirement request, cost due to announcing a voluntary retirement scheme and cost to the organisation due to one-time special payments to those who retire during the time period is discussed.
Keywords: Voluntary retirement schemes; Optimal withdrawal time; Manpower planning